The type of employment contract and employees' health and occupational functioning - The review of studies - Dorota Żołnierczyk-Zreda (Nofer Institute of Occupational Medicine, 2015)
From over 2 decades intensive research concerning temporary workers has been carried out in Europe and outside Europe. Despite having the highest rate of temporary workers in Europe, the studies on this topic are very rare in Poland. The aim of the study was to review the existing research on the relations between temporary work and employees' health and occupational functioning. The main conclusion from this review is that there is a significant inconsistency between the results of the studies included in this review due to such factors as heterogeneity of the group "temporary workers," cultural and generational differences between temporary workers, as well as different economic context in which those studies had been carried out. The main recommendations for the future research is thus to take into account the personal preferences for performing temporary work and to use more complex study design. Med Pr 2015;66(4):565-573